Data for - Spread of bacteria in soil - Otten, Wilfred; Eickhorst, Thilo; Juyal, Archana; Baveye, Philippe C. (Cranfield University, 2020)
Data set related to the paper 'Influence of soil structure on the spread of Pseudomonas fluorescens in soil at microscale' the objective of the study was to determine the influence of soil pore characteristics on the spread of bacteria in soil. Bacteria were introduced and locally and allowed to spread through soil. Soil was resin impregnated and the location of bacteria was observed in thin sections. X-ray CT was used to determine the physical characteristics of the pore space. The data set contains the raw data published in the accompanying paper. Treatment refers to the bulk density of the soil and 2 thin sections were counted for each sample. at each micro-site in soil pore characteristics are given in the table and the number of bacterial cells found in that section through observation and counting under the microscope. Counts are converted to cell densities. The data relate to the spread of bacteria and further analysis of the data is described in the paper
Keywords: X-Ray CT imaging; microscopy images; ecology; Soil Science; Soil Biology; Soil Physics